Baseline Clinical and Neuroimaging Biomarkers of Treatment Response to High-Frequency rTMS Over the Left DLPFC for Resistant Depression - Harika-Germaneau, Ghina; Wassouf, Issa; Le Tutour, Tom; Guillevin, Remy; Doolub, Damien; Rostami, Reza; Delbreil, Alexia; Langbour, Nicolas; Jaafari, Nematollah (Frontiers in Psychiatry, 2022)
Repetitive transcranial magnetic stimulation (rTMS) has proven to be an efficient treatment option for patients with treatment resistant depression (TRD). However, the success rate of this method is still low, and the treatment outcome is unpredictable.  The objective of this study is to explore clinical and structural neuroimaging factors as potential biomarkers of the efficacy of high-frequency (HF) rTMS (20Hz) over the left Dorso-Lateral Pre-Frontal Cortex (DLPFC). We analysed the records of 131 patients with mood disorders, who were treated with rTMS and were assessed at baseline, at the end of stimulation and one month after the end of treatment. The response is defined as a 50% decrease of the MADRS score between the first and last assessment. Each of these patients had a T1 MRI scan of the brain which was then segmented using Freesurfer. Whole-brain analyses (QDEC) were conducted and corrected for multiple comparisons. Responder status was also analyzed using binomial multivariate regression models. The explored variables were clinical, and anatomical features of the rTMS target obtained from T1 MRI: target-scalp distance, DLPFC grey matter thickness, and various cortical measures of interest studied in previous works. Binomial multivariate regression model results showed that type of depression (p=0.025), gender (p=0.010), depression severity (p=0.027), were found to be associated with response to rTMS. The resistance stage also showed a significant trend (p=0.055). Whole-brain analyses on volume revealed that the average volume of the left part of the superior frontal and caudal middle frontal regions are associated with the status of response. Other MRI-based measures are not associated significantly in our population with response to rTMS. In this study, we investigated the clinical and neuroimaging biomarkers associated with the response to High-Frequency rTMS over the left DLPFC in a large sample of TRD patients. Women, Bipolar Depressive Disorder (BDD) and less resistant patients respond better to HF rTMS. Responders present a lower volume of the left part of the superior frontal and caudal middle frontal. These results support further investigation into the use of clinical variables and structural MRI as a possible biomarker of rTMS treatment response.